(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the socio-ethical views of thinkers from the point of view of ideological and political interests, scientifically and theoretically explores the content and essence of their consequences for national and spiritual life. Also in the article, the socio-ethical views of thinkers are considered as an important part of our national spiritual heritage, and they are based on the greatness of our socio-ethical heritage left by our ancestors, and the need to master it in the context of the growing influence of “mass culture” on our national spirituality, consciousness and worldview of our youth.